Developing a Digital Tourism Guidebook Model for Community-Based Sustainable Tourism: Insights from Social Studies of Tourism in Nonthaburi and Bangkok, Thailand - Irena Novarlia; Dafa Dhiyaul Haq; Syaharuddin Syaharuddin; Oman Sukirman; Chasya Nadzira R (CV. Sakura Digital Nusantara, 2026)
Digital technologies have enhanced tourism accessibility, information sharing, and visitor engagement. However, most digital tourism initiatives remain destination-oriented and rarely integrate community knowledge, diaspora activities, halal tourism, and collaborative governance. This study develops and validates a digital tourism guidebook model for community-based sustainable tourism based on the socio-cultural, educational, religious, and halal tourism activities of the Indonesian Muslim diaspora community in Nonthaburi and Bangkok, Thailand. Using a qualitative case study, data were collected through interviews with ten key informants, participant observation, document analysis, and expert and stakeholder validation. Thematic analysis identified six themes: socio-cultural documentation, halal tourism and Islamic heritage, fragmented digital information, community participation, digital literacy, and responsible intercultural engagement. These findings informed a participatory digital guidebook model integrating community-generated content, intercultural storytelling, responsible visitor guidelines, collaborative governance, and continuous updating. The model was considered relevant, feasible, and culturally appropriate. This study conceptualizes the digital guidebook as a participatory knowledge platform supporting community empowerment, cultural preservation, and sustainable tourism governance.